Versatile, vigilance, and gut microbiome support the priority of high-ranking hens - Xie, Zhijiang; Xing, Limin; Zhao, Mengqiao; Zhao, Lei; Liu, Jinling; Li, Yushan; Gan, Jiankang; Chen, Siyu; Li, Hua (Frontiers in Veterinary Science, 2023)
Dominance hierarchy exists in social animals, and showed profound impacts on animals' survival, physical and mental health and reproductive success. Aggressive interaction, as the main indicator is used to calculate social hierarchy, however, is not found in some female animals. In this study, we aimed to figure out the establishment of social hierarchy in hens that nearly occur aggressive behaviors, and investigated the interactions of social hierarchy with production performance and gut microbiome. Forty 49-day-old Qingyuan hens were randomly divided into four groups. Social hierarchy of hens was calculated by the relative position around the feeder. The rank 1 (R1), R2, R3, R4, R5, R6, R7, R8, R9, and R10 birds were determined in ascending. Then, R1 and R2 birds (four duplicate, n = 8) were named as high-ranking hens (HR) group, while R9 and R10 individuals were named as low-ranking hens (LR) group (four duplicate, n = 8). The heart index (P = 0.01), number of visits per day, daily feed intake, and occupation time per day were higher in the HR group than LR group, but the LR group had higher feed intake per visit than HR group. The alpha diversity was significantly lower in the HR group than HR group (P = 0.05). The relative abundance of phylum Firmicutes was higher while that of phylum Deferribacterota was lower in the HR group than LR group (P < 0.05). At the genus level, the relative abundance of Succinatimonas, Eubacterium hallii group, and Anaerostipes was higher in HR group than in LR group. The relative abundance of Bacteroides, Mucispirillum, Subdoligranulum, and Barnesiellaceae unclassified was higher in the LR group than HR group (P < 0.05). In conclusion, rank of hens could be calculated by the relative position around the feeder when they compete for food. The dominant hens have a adaptive heart .Moreover, they are more vigilant and have the priority of foraging. Low-ranking hens adopt strategies to get enough food to sufficient themselves. Hens of high-ranking possess beneficial bacteria that use favorable substances to maintain the balance of gut environment.